Effect of ZnO nanoparticles on the sensitivity of cholesterol detection by cyclic voltammetry (SCIÉNDO INGENIUM, 2025)
In this work, the cyclic voltammetric response of the enzymatic carbon biosensor with ZnO nanoparticles (ZnO NPs) synthesized by the sol-gel route is reported, to determine the sensitivity of cholesterol detection. ZnO NPs with a wurtzite-type hexagonal structure with a hydrodynamic diameter of 11.5 nm were obtained, presenting absorbance in the UV region at 347 nm due to the formation of the exciton and with a band gap of 3.57 eV. The enzymatic carbon biosensor with ZnO NPs: COX / ZnO NPs / C, detected an increase in peak response current with increasing cholesterol concentration as well as an increase in Faradaic peak current with increasing cholesterol concentration due to the electronic transfer in the redox reaction that occurs at the biosensor-solution interface towards the electrode through its mediator, showing direct linearity between both variables from 25 mg/dL to 180 mg/dL, which was not detected without ZnO nanoparticles. The sensitivity of the biosensor was determined, obtaining a high value of 30.8 μAmM-1cm-2. ZnO nanoparticles improve the cholesterol detection sensitivity of the carbon biosensor since it immobilizes the enzymes by physical adsorption for a better interaction with cholesterol, improving the electronic transfer with the applied potential.
Keywords: Enzymatic carbon biosensor; ZnO nanoparticles; cholesterol; cyclic voltammetry; sensitivity